Effect of paternalistic leadership on Chinese youth elite athletes’ satisfaction: Resilience as a moderator - Liu, Pan; Li, Sitan; Zhang, Qi; Zhang, Xiumei; Guo, Lingling; Li, Juan (Frontiers in Psychology, 2022)
This study extended the research on the relationship between youth elite athletes' satisfaction and coaches' paternalistic leadership by identifying athletes' resilience as a moderator. A total of 221 youth elite football (i.e., soccer) players aged 13-19 years old who are students of a Chinese professional football boarding school participated in a questionnaire survey. The study found no correlation between the three dimensions of coaches' paternalistic leadership (authoritative leadership, benevolent leadership, and moral leadership) and the youth athletes' satisfaction. The results also showed that the interaction of resilience and moral leadership affects the youth elite athletes' satisfaction, whereas resilience does not play a moderating role in the relationship between authoritative leadership or benevolent leadership and satisfaction. As the results of the study are different from those of other scholars, they may reveal the uniqueness of youth elite football players in boarding schools. This study further analyzed the possible reasons for this result and prospected (or indicated) the theoretical and practical implications of these findings. Based on the conclusion, the study recommended that youth elite football schools should pay attention to the results of scientific research in leadership styles and apply them to practice in the future.